The world system and the Earth system : global socioenvironmental change and sustainability since the Neolithic - Hornborg, Alf; Crumley, Carole L. (Left Coast Press, 2006)
Contributors from a wide spectrum of disciplines, including archaeology, anthropology, geography, ecology, palaeo-science, geology, sociology, and history discuss the complex ways in which human culture, economy, and demographics interact with ecology and climate change.